Ответы и объяснения

2012-11-17T13:44:41+00:00

1) раскрываем скобки

6х²+6x-9x-6=0

приводим подобные

6х²-3х-6=0

а теперь решаем как обычное уравнение

6х²-3x=6

 

х=-2\3 или 3\2

Лучший Ответ!
2012-11-17T14:08:45+00:00

1)  2х-3=0   3х+2=0      2) 3х+2=-6     2х-3=-6   3)(2х-3)(3х+2)-(6х*2)=0

     2х=3       3х=-2           3х=-8        2х=-3           6х-6-12х=0 

     х=3/-2    х=-2/-3        х=-8/-3     х=-3/-2        -6х=6

                                                                          х=1